DETERMINING THE IMPORTANCE OF ETHICAL LEADERSHIP BASES FROM ISLAMIC PERSPECTIVE - Nassradin Moftah A Elwahayshe; Mohd Syakir Mohd Rosdi (International Journal of Accounting, Finance and Business, 2024)
In its theoretical aspect, the study sought to determine the importance of the pillars of ethical leadership from an Islamic perspective. The study followed a qualitative approach, and the study sample consisted of a group of directors of senior departments, deans of colleges, and academics specialized in the field of Islamic studies at an educational institution represented by the University of Zintan. Data for the qualitative study were collected through personal interviews. The results of the qualitative analysis of the participants’ answers confirmed the results of the theoretical study, as most of the participants agreed in their answers about the pillars that they consider important in building the concept of moral leadership from an Islamic perspective, which is a commitment to Islamic values, sincerity, honesty, trustworthiness, justice, and obedience to God. And sincerity in monotheism and following the example of His Noble Messenger (may God bless him and grant him peace) and the Rightly Guided Caliphs.